The double pulsar J0737-3039: testing the neutron star equation of state - Podsiadlowski, P; Dewi, J; Lesaffre, P; Miller, J; Newton, W; Stone, JR (Oxford University Press, 2005)
The double pulsar J0737--3039 has become an important astrophysical laboratory for testing fundamental physics. Here we demonstrate that the low measured mass of Pulsar B can be used to constrain the equation of state of neutron star matter {\em under the assumption} that it formed in an electron-capture supernova. We show that the observed orbital parameters as well as the likely evolutionary history of the system support such a hypothesis and discuss future refinements that will improve the constraints this test may provide.